Incidental Meniscal Findings on Knee MRI in Middle-Aged and Elderly Persons - Englund, Martin (2008)
BACKGROUND: Magnetic resonance imaging (MRI) of the knee is often performed in patients who have knee symptoms of unclear cause. When meniscal tears are found, it is commonly assumed that the symptoms are attributable to them. However, there is a paucity of data regarding the prevalence of meniscal damage in the general population and the association of meniscal tears with knee symptoms and with radiographic evidence of osteoarthritis. METHODS: We studied persons from Framingham, Massachusetts, who were drawn from census-tract data and random-digit telephone dialing. Subjects were 50 to 90 years of age and ambulatory; selection was not made on the basis of knee or other joint problems. We assessed the integrity of the menisci in the right knee on 1.5-tesla MRI scans obtained from 991 subjects (57% of whom were women). Symptoms involving the right knee were evaluated by questionnaire. RESULTS: The prevalence of a meniscal tear or of meniscal destruction in the right knee as detected on MRI ranged from 19% (95% confidence interval [CI], 15 to 24) among women 50 to 59 years of age to 56% (95% CI, 46 to 66) among men 70 to 90 years of age; prevalences were not materially lower when subjects who had had previous knee surgery were excluded. Among persons with radiographic evidence of osteoarthritis (Kellgren–Lawrence grade 2 or higher, on a scale of 0 to 4, with higher numbers indicating more definite signs of osteoarthritis), the prevalence of a meniscal tear was 63% among those with knee pain, aching, or stiffness on most days and 60% among those without these symptoms. The corresponding prevalences among persons without radiographic evidence of osteoarthritis were 32% and 23%. Sixty-one percent of the subjects who had meniscal tears in their knees had not had any pain, aching, or stiffness during the previous month. CONCLUSIONS: Incidental meniscal findings on MRI of the knee are common in the general population and increase with increasing age.